Respuesta :

Answer:

A. x^2−x+6

B. 2x^2−11x+12

C. x^2−4

Step-by-step explanation:

Hope it helps

A. Distribute:

=(x)(x)+(x)(−3)+(2)(x)+(2)(−3)

=x2+−3x+2x+−6

Combine Like Terms:

=x2+−3x+2x+−6

=(x2)+(−3x+2x)+(−6)

=x2+−x+−6

B. I can't find an explanation

C.  I can't find an explanation

Answer:

So we apply the distributive property to get

a) x^2 - 3x + 2x - 6

b) 2x^2 - 8x - 3x + 12

c) x^2 - 2x + 2x - 4

then we add like terms to get

a) x^2 - x - 6

b) 2x^2 - 11x + 12

c) x^2 - 4

brainliest please?